Two New Bioactive Furoquinoline Alkaloids from Zanthoxylum armatum - Samad, Abdul; Adeel, Muhammad; Khan, Dilfaraz; Badshah, Syed; Muhammad, Zia; Khan, Shafiullah; Hanra Han, Jane (Asian Journal of Chemistry, 2015)
The n-hexane, dichloromethane, ethyl acetate and n-butanol soluble fractions of Zanthoxylum armatum were screened for antifungal activity against Aspergillus flavus and Aspergillus niger. The dichloromethane soluble fraction of Zanthoxylum armatum inhibited the growth of Aspergillus flavus by 22.5 % and Aspergillus niger by 41.2 %, while the ethyl acetate soluble fraction compound decreased the growth of Aspergillus flavus and Aspergillus niger by 55.5 and 61 % respectively. The n-hexane and n-butanol fractions showed low inhibitions against these fungi. Further the chromatographic separation of the ethyl acetate fraction led to the isolation of two new furoquinoline alkaloids; 4-methoxy-12,12-dimethylcyclopenta furoquinoline-10-carbaldehyde and methyl 4-methoxy-12,12-dimethylcyclopenta furoquinoline-10-carboxylate. The isolated compounds were tested for antioxidant activities. The compound 1 was found more potent in both DPPH and ABTS radical scavenging assay.